The measurement of productivity in the construction industry : a detailed overview of productivity measurement developments and a proposed alternative method of measurement for the industry in South Africa - Louw, Willem (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1985.